Increasing Motivation Understanding The Material Converting Fractions To Percent And Decimal Form Through The Application Of The Problem Based Laerning (Pbl) Method For Class V Students Of SDN 2 Jambukulon Ceper - Muh Anwar Sahadat (Universitas Sebelas Maret, 2022)
This research aims to improve understanding of the material on changing fractions to percent and decimal form through the application of the Problem Based Learning (PBL) method for SDN 2 Jambukulon students in class V. The research carried out was classroom action research (PTK). This classroom action research was carried out as an effort to overcome problems that arise in class V. This research uses the problem based learning method. The subjects who took action were the class teachers and the subjects who took action were the 20 students in class V of SDN 2 Jambukulon. This PTK uses quantitative descriptive methods. Data collection in this study used written test techniques. This research was carried out in 2 stages, namely cycle I and cycle II. The data analysis technique uses quantitative descriptive data analysis.This research was carried out in two cycles. The results of the research show that the use of the problem based learning method can increase motivation to understand the material on changing fractions to percent and decimal form in students at SDN 2 Jambukulon in class V. In cycle I the data shows that 5 students (25%) got a score above 60. those classified as